2021
DOI: 10.3390/jcm10204659
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Wound Infiltration Use for Postoperative Pain Management: A Narrative Review

Abstract: Local anesthetic wound infiltration (WI) provides anesthesia for minor surgical procedures and improves postoperative analgesia as part of multimodal analgesia after general or regional anesthesia. Although pre-incisional block is preferable, in practice WI is usually done at the end of surgery. WI performed as a continuous modality reduces analgesics, prolongs the duration of analgesia, and enhances the patient’s mobilization in some cases. WI benefits are documented in open abdominal surgeries (Caesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 252 publications
(393 reference statements)
1
27
0
3
Order By: Relevance
“… 39 , 40 Since the systemic toxicity of LIA can affect up to 11% of patients, the post-op monitoring of LIA patients cannot be ignored. 41 A similar observation was made by Tian et al; their retrospective TKA study showed that the short-term analgesic effect of LIA was similar to that of nerve block and reduced the need for opiate supplementation, and that LIA and nerve block had similar complication rates. 42 There is also evidence of marginal early post-op pain management improvement in patients treated by LIA as compared to peripheral nerve block, when evaluated 24 hours post-op.…”
Section: Discussionsupporting
confidence: 72%
“… 39 , 40 Since the systemic toxicity of LIA can affect up to 11% of patients, the post-op monitoring of LIA patients cannot be ignored. 41 A similar observation was made by Tian et al; their retrospective TKA study showed that the short-term analgesic effect of LIA was similar to that of nerve block and reduced the need for opiate supplementation, and that LIA and nerve block had similar complication rates. 42 There is also evidence of marginal early post-op pain management improvement in patients treated by LIA as compared to peripheral nerve block, when evaluated 24 hours post-op.…”
Section: Discussionsupporting
confidence: 72%
“…Patients should receive some form of local or regional anaesthesia, as this is effective for controlling movement-evoked pain (Shanthanna et al, 2021). Wound infiltration is simple to carry out and inexpensive (Stamenkovic et al, 2021). The infrequent use of wound infiltration was not explained by frequent use of regional anaesthesia.…”
Section: Obstetrics and Gynaecology Urologymentioning
confidence: 99%
“…Sowohl bei der Thorakotomie als auch bei der thorakoskopischen Chirurgie (video-assisted thorascopic surgery, VATS) hat sich gezeigt, dass die lokale Wundinfiltration (LWI) zu niedrigeren Schmerzscores und einem geringeren Analgetikaverbrauch führte. Außerdem konnten die Autoren anderer aktueller Studien zeigen, dass mit der LWI im Vergleich zum Placebo die Patientenzufriedenheit erhöht, die Mobilisation früher erfolgen, und somit der postoperative Krankenhausaufenthalt verkürzt werden konnte [1, 2].…”
Section: Transfer In Die Praxis Von Prof Dr Khosro Hekmat (Köln)unclassified